Search for exclusive Z-boson production and observation of high-mass pp[over ]-->pgammagammap[over ]-->pl;{+}l;{-}p[over ] events in pp[over ] collisions at sqrt[s]=1.96 TeV. - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; Alvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; et al. (2009)
This Letter presents a search for exclusive Z boson production in proton-antiproton collisions at sqrt[s]=1.96 TeV, using the CDF II detector. No exclusive Z-->l;{+}l;{-} candidates are observed and the first upper limit on the exclusive Z cross section in hadron collisions is found to be sigma_{excl}(Z)<0.96 pb at 95% confidence level. In addition, eight candidate exclusive dilepton events from the process pp[over ]-->pgammagammap[over ]-->pl;{+}l;{-}p[over ] are observed, and a measurement of the cross section for M_{ll}>40 GeV/c;{2} and |eta_{l}|<4 is found to be sigma=0.24_{-0.10};{+0.13} pb, which is consistent with the standard model prediction.